2018
DOI: 10.5194/ascmo-4-1-2018
|View full text |Cite
|
Sign up to set email alerts
|

The joint influence of break and noise variance on the break detection capability in time series homogenization

Abstract: Abstract. Instrumental climate records of the last centuries suffer from multiple breaks due to relocations and changes in measurement techniques. These breaks are detected by relative homogenization algorithms using the difference time series between a candidate and a reference. Modern multiple changepoint methods use a decomposition approach where the segmentation explaining most variance defines the breakpoints, while a stop criterion restricts the number of breaks. In this study a pairwise multiple breakpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
(38 reference statements)
5
33
0
Order By: Relevance
“…Using very high time frequency data series increases, for example, the noise of time series. Lindau and Venema (2018) showed that for a pairwise multiple breakpoint algorithm, the results for low signal‐to‐noise ratios (SNRs) do not differ much from random segmentations and that reliable break detection at low but realistic SNRs needs a new approach. However, a break identified by on the methods assessed here can be adjusted for in the individual observation series, and these homogenized individual data points can then be used for weather and climate extreme applications and assimilation into reanalysis products.…”
Section: Discussionmentioning
confidence: 99%
“…Using very high time frequency data series increases, for example, the noise of time series. Lindau and Venema (2018) showed that for a pairwise multiple breakpoint algorithm, the results for low signal‐to‐noise ratios (SNRs) do not differ much from random segmentations and that reliable break detection at low but realistic SNRs needs a new approach. However, a break identified by on the methods assessed here can be adjusted for in the individual observation series, and these homogenized individual data points can then be used for weather and climate extreme applications and assimilation into reanalysis products.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to decide which number of breaks is optimal a stop criterion is needed that penalizes the insertion of breaks. Caussinus and Mestre (2004), Domonkos (2011a) and Lindau and Venema (2018a) use the Lyazrhi stop criterion (Caussinus and Lyazrhi, 1997), which is given by…”
Section: Fraction Of Undetected Breaksmentioning
confidence: 99%
“…For the ideal case without noise, Lindau and Venema (2018a) showed that the explained variance grows with k by…”
Section: Fraction Of Undetected Breaksmentioning
confidence: 99%
“…This suggests that stairs are easier to detect than platforms, although also gradual inhomogeneities modelled as linear trends in the station data could have lowered the percentage of detected platforms. The percentage of stairs and platforms as they are detectable by a homogenization algorithm will be further dependent, e.g., on the signal-to-noise ratio (SNR), which is shown to be a key parameter for break detection (Lindau and Venema, 2016;Lindau and Venema, 2018a). Thus, to conclude that the reduced number of detected platforms is directly caused by an admixture of BM-type breaks is risky and has been a motivation for this further study.…”
Section: The Different Characteristics Of Brownian Motion and Random mentioning
confidence: 99%